The Feeling of “Face” in Confucian Society: From a Perspective of Psychosocial Equilibrium - Han, Kuei-Hsiang (Frontiers in Psychology, 2016)
Previous research on the feeling of “face” has long described “face” as a complicated phenomenon in Confucian societies. Indeed, the feeling of face is highly context dependent. One may have very different (having or losing) face perception if the same face event occurs in a different context. To better capture the features of how face is felt, effects on possible responses need to be considered. Therefore, this article adopts a perspective of psychosocial equilibrium to elaborate people’s feeling of face in Taiwan, a Confucian society. The first section illustrates the concept of psychosocial equilibrium and its psychodynamic effects on people’s feeling of face. Then, the second section of this article takes positive social situations (having face events) as backdrop to exhibit how people balance their psychosocial equilibrium with different relationships. Following the positive social situations, the third section of this article then focuses on the negative situations (losing face events) to explain how losing face is felt due to unbalance of psychosocial equilibrium with one’s relation in that specific context.